Possible association of fimA genotype of Porphyromonas gulae with the severity of periodontal disease and the number of permanent teeth in dogs - Shirahata, So; Iwashita, Naoki; Sasaki, Rie; Nomura, Ryota; Murakami, Masaru; Yasuda, Junya; Yasuda, Hidemi; Nakajima, Kuniyasu; Inaba, Hiroaki; Matsumoto-Nakano, Michiyo; Nakano, Kazuhiko; Uchiyama, Jumpei; et al. (Frontiers in Veterinary Science, 2023)
Previous research has demonstrated that Porphyromonas gulae (P. gulae) significantly contributes to the development of periodontal disease in dogs. P. gulae is divided into three subtypes according to the 41-kDa filamentous appendage (fimA), defined as types A, B, and C. This study aimed to elucidate the association between fimA type of P. gulae with the number of permanent teeth, reflecting the severity of periodontal disease. 225 dogs were categorized by P. gulae fimA type as negative, type A dominant, type B dominant, and type C dominant. The stage of periodontal disease in P. gulae-positive dogs increased with age, particularly in type C dominant dogs. Correspondingly, the number of permanent teeth in P. gulae fimA type C-dominant dogs was significantly lower than that of P. gulae-negative dogs, suggesting there is a significant association between fimA type of P. gulae and the number of permanent teeth resulting from the development of periodontal disease.